Featured Cover. Issue 3 (16th March 2022) - Hayer, Rupinder; Kirley, Kate; Cohen, Jordana B.; Tsipas, Stavros; Sutherland, Susan E.; Oparil, Suzanne; Shay, Christina M.; Cohen, Debbie L.; Kabir, Christopher; Wozniak, Gregory
Abstract : The cover image is based on the Original Article Using web‐based training to improve accuracy of blood pressure measurement among health care professionals: A randomized trial by Rupinder Hayer et al., https://doi.org/10.1111/jch.14419 .